Green Marketing Management in the Digital Era: A Study of Website Content and Corporate Social Media in Surabaya - Endah Budiarti; Ulfi Pristiana; Nekky Rahmiyati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The development of environmental issues and digital transformation has encouraged companies to adopt green marketing strategies as part of modern marketing management. This study aims to analyze green marketing management in the digital era through a study of website content and social media of companies operating in Surabaya. The research uses a descriptive qualitative approach with content analysis on digital content from official websites and social media platforms. Data were collected through non-participant observation and digital documentation and analyzed using thematic coding. The results show that company websites are mainly used to communicate sustainability information in a formal and credible way, while social media supports more persuasive, visual, and interactive communication. Dominant green marketing themes include environmental commitment, CSR activities, environmental campaigns, and consumer education. Although most companies show consistent messages across websites and social media, differences remain in the depth of information and signs of greenwashing risks, especially in social media content. This study concludes that the effectiveness of digital green marketing is determined by consistency, transparency, and the suitability of communication strategies with digital media characteristics. These findings are expected to serve as a reference for companies in managing green marketing sustainably.